2017
DOI: 10.3390/ma10060624
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Surface Morphology and Impact Strength of Cellulose/PLA Composites

Abstract: Polylactide (PLA)-based composite materials reinforced with ball-milled celluloses were manufactured by extrusion blending followed by injection molding. Their surface morphology from impact fracture were imaged with scanning electron microscopy (SEM) and investigated by calculating their fractal dimensions. Then, linear regression was used to explore the relationship between fractal dimension and impact strength of the resultant cellulose/PLA composite materials. The results show that filling the ball-milled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…This behavior was supported by a rough and irregular fractured surface in PLA‐b‐CNCs nanocomposites observed from SEM images (Figure ). Similar results were reported by Gao and Qiang who showed higher impact strength for PLA‐based nanocomposites with a rougher fractured surface.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This behavior was supported by a rough and irregular fractured surface in PLA‐b‐CNCs nanocomposites observed from SEM images (Figure ). Similar results were reported by Gao and Qiang who showed higher impact strength for PLA‐based nanocomposites with a rougher fractured surface.…”
Section: Resultssupporting
confidence: 90%
“…However, nanocomposites with 1 and 3 wt % b‐CNCs exhibited rough and irregular surfaces, suggesting the ductile fracture mechanism in PLA‐1b‐CNCs and PLA‐3b‐CNCs nanocomposites. In general, the fractured surface can illustrate the impact resistance of the materials . The rough and irregular fractured surface in PLA‐b‐CNCs nanocomposites indicated more required work for impact fracture as compared with PLA‐CNCs nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was supported by the morphological study by Mohammadalipour et al, which revealed similar images for their neat epoxy composite. The river marking zones were also observed by H. Gao and T. Qiang through SEM analysis of a virgin PLA composite using a larger magnification, confirming that the unfilled composite exhibited a brittle fracture pattern.…”
Section: Resultsmentioning
confidence: 56%
“…Differential scanning calorimetry (DSC) Figure 4 displays the second heating DSC curves of pure PLA, pure PBAT and PLA/PBAT blends with varying PBAT contents. The second heating curves were chosen to remove previous thermal history and to make T g clearer and more obvious as stated by (Jiang et al 2006, Gao andQiang 2017). From the DSC curves in figure 4, T g of PBAT was absent due to T g of PBAT was reported at −37°C (Signori et al 2015) (Carbonell-Verdu et al 2018).…”
Section: Thermal Propertiesmentioning
confidence: 99%